Higher levels of social and material deprivation are associated with higher rates of influenza-like illness–related emergency department visits: Edmonton, Alberta, 2004–2014. (December 2020) - Martin, L.J.; Chen, Y.; Serrano-Lomelin, J.; Talbot, J.; Yasui, Y.
Abstract: Objectives: Neighbourhood-level deprivation is associated with hospitalization related to respiratory infections; however, hospitalizations exclude many who seek care with less severe respiratory illnesses. Another major seasonal contributor to respiratory illness-associated healthcare burdens are influenza-like illness (ILI)–related emergency department (ED) visits. We investigated associations between area-level social and material deprivation and ILI-related ED use. Study design: This is a retrospective ecological study. Methods: We linked ILI-related ED visit data (2004–2014) for Edmonton, Alberta to a Canadian area-level material and social deprivation index, categorizing deprivation into quintiles. Using a multivariable Poisson model with log population as the offset, we modelled the relationship between visit rates and material and social deprivation adjusting for week and season, age, sex and the interaction between age and sex. Results: We included 67, 585 ILI-related ED visits, representing 1075.5 (95% confidence interval (CI) = 1067.4–1083.6) visits per 100, 000 person-years. ILI-related visit rates increased as each of material and social deprivation increased; increases were slightly greater for material deprivation. Comparing the most deprived quintile to the least deprived quintile: for material deprivation, ILI-related ED visit rates were two times higher (rate ratio (RR) = 2.00, 95% CI = 1.96–2.05); and, for social deprivation, one-and-a-half times higher (RR = 1.47, 95% CI = 1.44–1.51). Conclusions: Higher area-level material and social deprivation were associated with higher ILI-related ED visit rates. These findings can be used to identify areas that may need additional public health and healthcare resources and to improve targeting of prevention strategies. Understanding differentials in healthcare use such as this may be especially relevant to ensuring equity of outcomes for pandemic preparedness planning. Highlights: Area-level deprivation was associated with higher influenza-like illness (ILI)-related emergency department visit rates. Visit rate increases were slightly greater for material than for social deprivation. Results may help target prevention strategies and improve equity of outcomes for pandemic preparedness planning.